Biocompatible DNA/5-Fluorouracil-Gemini Surfactant-Functionalized Gold Nanoparticles as Promising Vectors in Lung Cancer Therapy - Rosa M. Giráldez-Pérez; Elia Grueso; Inmaculada Domínguez; Nuria Pastor; Edyta Kuliszewska; Rafael Prado-Gotor; Francisco Requena-Domenech (MDPI AG, 2021)
The design and preparation of novel nanocarriers to transport cancer drugs for chemotherapy purposes is an important line of research in the medical field. A new 5-fluorouracil (5-Fu) transporter was designed based on the use of two new biocompatible gold nanosystems: (i) a gold nanoparticle precursor, Au@16-Ph-16, stabilized with the positively charged gemini surfactant 16-Ph-16, and (ii) the compacted nanocomplexes formed by the precursor and DNA/5-Fu complexes, Au@16-Ph-16/DNA-5-Fu. The physicochemical properties of the obtained nanosystems were studied by using UV-visible spectroscopy, TEM, dynamic light scattering, and zeta potential techniques. Method tuning also requires the use of circular dichroism, atomic force microscopy, and fluorescence spectroscopy techniques for the prior selection of the optimal relative Au@16-Ph-16 and DNA concentrations (R = CAu@16-Ph-16/CDNA), biopolymer compaction/decompaction, and 5-Fu release from the DNA/5-Fu complex. TEM experiments revealed the effective internalization of the both precursor and Au@16-Ph-16/DNA-5-Fu-compacted nanosystems into the cells. Moreover, cytotoxicity assays and internalization experiments using TEM and confocal microscopy showed that the new strategy for 5-Fu administration enhanced efficacy, biocompatibility and selectivity against lung cancer cells. The differential uptake among different formulations is discussed in terms of the physicochemical properties of the nanosystems.